1998
DOI: 10.1109/72.701183
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian retrieval in associative memories with storage errors

Abstract: Abstract-It is well known that for finite-sized networks, onestep retrieval in the autoassociative Willshaw net is a suboptimal way to extract the information stored in the synapses. Iterative retrieval strategies are much better, but have hitherto only had heuristic justification. We show how they emerge naturally from considerations of probabilistic inference under conditions of noisy and partial input and a corrupted weight matrix. We start from the conditional probability distribution over possible pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…We commence from the result proven in Appendix A, namely that a family of functions, not a single function, all give identical values of and, hence, identical performance for pattern recovery, subject to our model of pattern distributions. Moreover, in Appendix A we show that simplified recall performance measure (and, in fact, the overall performance of any RCAM) remains invariant under similarity transformation (24) of the excitation function . Here and are arbitrary constants.…”
Section: A Optimal Excitation Function Formentioning
confidence: 99%
See 3 more Smart Citations
“…We commence from the result proven in Appendix A, namely that a family of functions, not a single function, all give identical values of and, hence, identical performance for pattern recovery, subject to our model of pattern distributions. Moreover, in Appendix A we show that simplified recall performance measure (and, in fact, the overall performance of any RCAM) remains invariant under similarity transformation (24) of the excitation function . Here and are arbitrary constants.…”
Section: A Optimal Excitation Function Formentioning
confidence: 99%
“…For instance, McEleice et al [23] have shown that all of the patterns stored in the Hopfield memory are recoverable provided that and that that the target memory pattern is within a Hamming distance of the input pattern. However, other studies [24], [28], [26] have suggested a limit of based on vanishingly small levels of noise. The density of memory bits in this case is, therefore, 0.14 bits per synapse [24].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Ref. [11] showed how iterative retrieval strategies emerge naturally from considerations of probabilistic inference under conditions of noisy and partial input and a corrupted weight matrix. A description of the development of neural network models for noise reduction is given in [12].…”
Section: Introductionmentioning
confidence: 99%